Persepsi Wajib Pajak Terhadap Penerapan Ter PPH Pasal 21 - Christina Dwi Astuti; Anne Monica Sijabat (Economic Reviews Journal, 2024)
This study aims to analyze the perceptions of taxpayers by conducting surveys using questionnaires and analyzing the perceptions of these taxpayers regarding the existence of a regulatory change in the Income Tax Law that examines the application of Income Tax Article 21 TER as the basis for calculating income tax. This research uses descriptive methods. The sampling procedure uses purposive sampling technique. The sample and population used in this study are taxpayers who have worked, taxpayers who have been registered as taxpayers, and who have paid & deposited at least once. 216 respondents were obtained. The research results of this study are (i) taxpayers have an agreed perception of the tax socialization of taxpayers on the application of Income Tax Article 21 TER (ii) taxpayers have an agreed perception of the understanding of tax regulations on the application of Income Tax Article 21 TER (iii) taxpayers have an agreed perception of taxpayer awareness of the application of Income Tax Article 21 TER.